2021
DOI: 10.21037/qims-20-902
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous hepatic iron and fat quantification with dual-energy CT in a rabbit model of coexisting iron and fat

Abstract: Background: Liver iron and fat are often co-deposited, synergistically aggravating the progression of chronic liver disease. Accurate determination of liver iron and fat content is helpful for patient management.To assess the accuracy of hepatic iron/fat decomposition using dual-energy computed tomography (DECT) for simultaneously quantifying hepatic iron and fat when both are present.Methods: Sixty-eight New Zealand rabbits on a high-fat/cholesterol diet plus iron injections were used to establish a model of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 27 publications
(42 reference statements)
0
8
0
1
Order By: Relevance
“…The recent technical advance of dual-source dualenergy CT (DS-DECT) has improved the situation, as this method uses two different X-ray sources, allowing for the simultaneous use of two different energies to achieve potential tissue differentiation. The advanced quantitative technique can separate several types of substances, such as water, iodine, calcium, uric acid, and fat (8)(9)(10)(11). Quantitative iodine parameters have been considered a promising tool for distinguishing malignant from benign tumors (12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…The recent technical advance of dual-source dualenergy CT (DS-DECT) has improved the situation, as this method uses two different X-ray sources, allowing for the simultaneous use of two different energies to achieve potential tissue differentiation. The advanced quantitative technique can separate several types of substances, such as water, iodine, calcium, uric acid, and fat (8)(9)(10)(11). Quantitative iodine parameters have been considered a promising tool for distinguishing malignant from benign tumors (12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike SECT, which underestimates fat in the presence of iron and vice versa, several phantom and animal studies have shown that DECT can accurately quantify iron, even in the presence of fat 52 82 83 and vice versa. 52 83 84 In contrast, several other studies have suggested that iron and fat affect the measurement of each other on DECT.…”
Section: Hepatic Ironmentioning
confidence: 99%
“…Unlike SECT, which underestimates fat in the presence of iron and vice versa, several phantom and animal studies have shown that DECT can accurately quantify iron, even in the presence of fat 52 82 83 and vice versa. 52 83 84 In contrast, several other studies have suggested that iron and fat affect the measurement of each other on DECT. 85 86 87 A recent study also suggested that the phase of contrast-enhanced scan (arterial, portal venous, and delayed) significantly affects the hepatic iron measurements on DECT.…”
Section: Hepatic Ironmentioning
confidence: 99%
“…Therefore, valid fat quantification in the presence of iron is necessary. While it is known that fat contents are underestimated in the presence of iron in dual-source CT [ 16 , 17 ], the potential impact of iron on dlCT fat quantification and how to deal with it was not clear, yet.…”
Section: Introductionmentioning
confidence: 99%